Economic value added for competitive advantage : a case of Indian enterprises - Saurabh (Cambridge Scholars Publishing, 2019)
Economic Value Added (EVA®) has been a much discussed concept that has assisted in the turnaround of a number of multinational enterprises across the world. It is based upon the theory of 'economic profit' that enables companies to capture and create wealth both for themselves and their stakeholders. The strategic decisions of performance and posturing can be grounded upon gaining competitive advantage through mapping economic profits. Existing studies on competitive advantage primarily discuss the meaning, definitions, and sources thereof. However, there are few contributions that discuss how.